Objectification and Exploitation of Women's Students Content in Social Media - Moh Toyyib; Dicky Nur Rahman; Moh Hamim Assidiki; Zainullah; Agoes Moh Moefad (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to examine more deeply how female students become objectified and exploited on social media. The contribution of this research is to fill the existing knowledge gap and provide a deeper understanding of the phenomenon of highlighting female students, who are a vulnerable group to exploitation and abuse. This research also pays attention to the negative impact of exploitation content that can harm female students physically, emotionally, and socially. The main motive of female students on social media is because they want to project a pious identity into a place to form a personal popularity existence on behalf of piety. Researchers used the Digital Ethnography approach to identify narratives, images and videos that show the exploitation of female students. The results and implications of this research can be a guide for women, especially female students.